Development of Geogebra Learning Media Based on Statistical Reasoning on Statistics Materials of Junior High School Students and its Influence for the Inteligent of Student - Intan Sari Rufiana1, Cholis Sa’dijah2, Subanji3, Hery Susanto4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This research aimed to develop geogebra learning media based on statistical reasoning. For the purpose of this research and development, ADDIE model by Dick & Carry was used. This research and development produced geogebra learning media based on statistical reasoning for junior high school students. Class environment that applies technology based on statistical reasoning is another variable besides genetic which is adaptive. The integration of new technologies for education is no longer an alternative; it has become an obligation and even guidance to develop these knowledge-sided. Through geogebra, students are directed to build their knowledge not just to memorize rules. The class that applies technology based on this statistical reasoning will develop students’ intelligence